Desain Materi Praktikum Pelayangan Bunyi Menggunakan Alat Musik Tiup dan Software Adobe AuditionTM 1.5 - Isnaini, Isnaini; Anwar, Khairil; Fadhya, Fadhya; Bunaiyah, Bunaiyah; Nurfaizal, Nurfaizal (UNIVERSITAS INDRAPRASTA PGRI, 2023)
One of the few sound phenomena is the beat. The concept of beat is very important to be study because its applies to daily life, but in teaching and learning activities most teachers are still in a conventional model theoretical-based, of course only give abstract knowledge to learners. On the other hand, the learning concept of wave must involve representations all (audio visual, graphical, mathematical, symbolic, and verbal). There have been many published papers on similar experiments. However, we continue to gather experiments using traditional musical instruments as a source of sound and free software tracker. Therefore, in this paper we will describe a conceptual teaching innovation by presenting a step by step how to do that using Sundanese flute from West Java (Indonesia) and Adobe audition 1.5, as well as examples of its application to determining the frequency of traditional musical instruments which is identical by the concept of beat, so it can be an interesting method to do in classroom.